The Impact of Profitability, Leverage, and Firm Size Toward Tax Avoidance in Coal Companies Listed on the Indonesia Stock Exchange - Louis Yosen Primsa Tarigan; Sally Yustin (Universitas Pelita Harapan, 2025)
The objective of this research is to analyze the impact of profitability, leverage, and firm size toward tax avoidance in coal companies listed on the Indonesia Stock Exchange for the period of 2020 to 2022. The independent variables used in this research are profitability measured by Return on Assets Ratio (RoA), leverage measured by Debt-to-Equity Ratio (DER) and firm size measured by total assets. Meanwhile, the dependent variable in this research is tax avoidance measured by Effective Tax Rate (ETR). The population in this research is coal companies listed on the Indonesia Stock Exchange for the period of 2020 to 2022, in which the samples are determined by using the Purposive Sampling Method, resulting in 11 companies selected with a total of 33 samples. The data analysis method used descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis tests, which are processed utilizing SPSS 26. The research result shows that profitability and leverage partially do not have significant impact toward tax avoidance. Meanwhile, firm size partially has a significant impact toward tax avoidance. Moreover, profitability, leverage, and firm size simultaneously have a significant impact toward tax avoidance.